2021
DOI: 10.1101/2021.02.15.431139
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of a biolistic delivery of fluorescent markers and CRISPR/Cas9 to the pollen tube

Abstract: In recent years, genome-editing techniques, such as the CRISPR/Cas9 system, have been highlighted as a new approach to plant breeding. Agrobacterium-mediated transformation has been widely utilized to generate transgenic plants by introducing plasmid DNA containing CRISPR/Cas9 into plant cells. However, this method is generally applicable to a limited range of plants, such as model species. To overcome this limitation, we developed a method to genetically modify male germ cells without the need for Agrobacteri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…In the case of bombardment, pollen germination occurs before the expression of the transgene; therefore, pollen germination and pollination of isolated pollen cannot be studied (Nagahara et al, 2021). Transgenic 35Sp::H2B-tdTomato was used for pollen germination analysis, and AtUBQ10p::tdTomato pollen grains were used for pollination analyses as target pollen expressing fluorescent proteins.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the case of bombardment, pollen germination occurs before the expression of the transgene; therefore, pollen germination and pollination of isolated pollen cannot be studied (Nagahara et al, 2021). Transgenic 35Sp::H2B-tdTomato was used for pollen germination analysis, and AtUBQ10p::tdTomato pollen grains were used for pollination analyses as target pollen expressing fluorescent proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Pollen germination is possible not only in the media but also on the pistil. We have previously reported that bombarded pollen can elongate pollen tubes on the pistil and reach the ovule (Nagahara et al, 2021). Our results suggest that pollination with isolated pollen may achieve efficient seed production from the target pollen (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations